TRAINING, ASSISTANCE, AND ANALYSIS OF MSME DEVELOPMENT STRATEGIES IN KARYAWANGI VILLAGE, WEST BANDUNG REGENCY - Rini Mulyani Sari; Evan Nugraha; Khaerul Rizal Abdurahman; Rosmini Ramli; Mochamad Vrans Romi; Sri Hastuti (Yayasan Education and Social Center, 2021)
MSME business owners face various obstacles: sales reductions, difficulty obtaining raw materials, limited distribution, finance difficulties, and production delays. The action research approach is used in this study. Participants in social situations participate in collective inquiry and self-reflection to improve the rationality and justice of their own social or educational activities and their understanding of these practices and the conditions under which they take place. This community service project has three parts: training, mentoring, and evaluation. The training activities took place on Saturday, September 18, 2021, at the Karyawangi Village Hall in Parongpong District, while the mentoring and assessment took place on Sunday, September 26, 2021, at the home of Mrs. Ani, an SME owner who participates in community service activities. The combination of SWOT and the Balanced Scorecard as an alternative method for growing SMEs at Karyawangi Village, West Bandung Regency